cis-Acting elements and trans-acting factors involved in the transcriptional control of the allantoicase (DAL2) gene in Saccharomyces cerevisiae - Willemse, Quintus,1968- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1994.